The Clinical Spectrum, Aetiology and Disease Progression of Children with Post-infectious Bronchiolitis Obliterans at Tertiary Paediatric Pulmonology Service in Cape Town, South Africa - Yassin, Aamir (Department of Paediatrics and Child Health, 2022)
Introduction: There is limited literature on chronic obstructive airway disease in the paediatric age group. Post-infectious bronchiolitis obliterans (PIBO) is a cause of obstructive airway disease children, with limited data in African children. Aim: To describe the clinical spectrum, aetiology, and disease progression of children with post-infectious bronchiolitis obliterans. Methodology: This is a cross sectional descriptive study included all patients aged 6 months to 15 years with PIBO attending a tertiary paediatric pulmonology service in Cape Town, South Africa over period of one year (November 2019 to October 2020). Results: Fifty-one patients with PIBO were enrolled, 78% were males, median age 60 months (IQR 33-107). The median age at disease presentation was 6 months (IQR 3-12), 80% initially presented with cough. Ninety-four percent of patients required hospital admission, 76% were admitted to ICU, 92% required supplemental oxygen therapy and 75% required ventilatory support. Reported cigarette smoke exposure was high (47%). Adenovirus was the most common cause of initial infection 59%. Lung hyperinflation (84%) and air trapping (78%) were the most common current chest radiographic findings; bronchiectasis in 45% of patients. Spirometry showed mixed (41.4%) or obstructive (27%) patterns, mean (SD) FEV1 z-score - 3.3(±1.4), FVC z-scores -2.4(±1.6) and FEV1/FVC z-score -3.1(±2.4). Corticosteroids were used during initial presentation in 92% of patients. Seventy six percent of patients required two or more hospital admissions. Cough (43%) and wheeze (39%) were the commonest reported current symptoms. Lung function impairment was associated with younger age at first presentation and recurrent hospital admissions. Children with higher BMI at presentation had higher FEV1/FVC z-score in later life. Improvement of symptoms over time was reported among 82% of patients. Conclusion: PIBO is a relatively common cause of chronic lung disease in South African children, with adenovirus being the commonest preceding illness. Symptoms of airway obstruction persist over time, but showed improvement with treatment, which included corticosteroids.